"Living Well" Trajectories Among Family Caregivers of People With Mild-to-Moderate Dementia in the IDEAL Cohort. (7th July 2022) - Clare, Linda; Gamble, Laura D; Martyr, Anthony; Sabatini, Serena; Nelis, Sharon M; Quinn, Catherine; Pentecost, Claire; Victor, Christina; Jones, Roy W; Jones, Ian R; Knapp, Martin; Litherland, Rachael; et al.
Abstract: Objectives: Understanding whether and how caregivers' capability to "live well" changes over time, and the factors associated with change, could help target effective caregiver support. Methods: We analyzed 3 time points (12 months apart) of Improving the experience of Dementia and Enhancing Active Life (IDEAL) cohort data from coresident spouse caregivers of community-dwelling individuals who had mild-to-moderate dementia at baseline, using latent growth and growth mixture models. Capability to "live well" was derived from measures of quality of life, well-being, and satisfaction with life. Results: Data from 995 spouse caregivers at Time 1, 780 at Time 2, and 601 at Time 3 were included. The mean "living well" score decreased slightly over time. We identified 3 classes of caregivers: one with higher baseline scores declining slightly over time (Stable; 66.8%), one with low baseline scores remaining stable (Lower Stable; 26.0%), and one with higher baseline scores showing marked decline (Declining; 7.2%). Scores on baseline measures differentiated the Lower Stable, but not the Declining, from the Stable class. Longitudinally, the Declining class was associated with care recipient cognitive decline and increasing hours providing care, as well as caregiver stress and depression. Findings were similar when caregivers with other kin relationships were included. Discussion: The findings indicate the importance of prompt identification of, and support for, caregivers at risk of the declining capability to "live well" and may assist in identifying those caregivers who could benefit most from targeted support.